Tips for the creation and application of effective operating procedures. Issue 4 (23rd January 2014) - Scholtz, Colin R.; Maher, Steven T.
<x xml:space="preserve">Abstract</x> Specific requirements exist in all Safety Management Systems Requirements (e.g., Process Safety Management and Risk Management Program) for the creation, content, and periodic update of operating procedures (OP). However, the development and actual implementation of OP has challenges that often result in deficiencies, regulatory citations, and in some cases, unfortunate tragedies. Although OP concepts involve the straightforward documentation of specific steps for safe and effective operation, many process facilities struggle with: securing the focus from operations personnel for the creation of quality procedures securing feedback from operations personnel if procedural steps do not coincide with actual practices ensuring the steps outlined in procedures avoid introducing additional process hazards creating procedures that are in a user‐friendly format identifying the most effective level of information and depth to include in the procedure addressing all modes of operations, including defining appropriate responsibilities Good‐quality OP are critical for encapsulating operational best practices and also provide a basis for ensuring consistent quality assurance. The objective of this article is to convey an understanding of the challenges that must be considered with the development of OP and provide specific examples that will facilitate the creation and ongoing application of OP. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 350–354, 2014